PENDEKATAN DUALISTIK TERHADAP KASUS UJARAN KEBENCIAN BERDASARKAN PANCASILA - Sulistya Eviningrum (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
Abstract— The spread of hate speech is very dangerous for the life of the Indonesian state, so it must be seriously addressed through legal means. Law enforcement for the prohibition of hate speech must be oriented towards creating a just legal decision. The dominance of a monoistic approach in law enforcement against hate speech is criticized because it is very prone to abuse. A monoistic approach that emphasizes fulfilling the elements of the offense must be evaluated because the main subject being tested or tried in cases of hate speech is utterances or words. Utterances or words have an interpretation, therefore to ascertain whether the perpetrators of hate speech really intend or intentionally spread information that can cause hatred based on Ethnicity, Religion, Race and Intergroup (SARA), the perpetrator's mental attitude when conveying the message. The dualistic approach is important to clearly describe whether the elements of the offense are fulfilled and the perpetrator's actions can be legally justified. The dualistic approach in law enforcement against hate speech is more likely to present justice in accordance with the values ??contained in Pancasila.